'I Feel … Slightly out of Touch': a Longitudinal Study of Teachers Learning to Teach English Pronunciation over a Six-Year Period. (1st March 2021) - Burri, Michael; Baker, Amanda
Abstract: Recent longitudinal studies have contributed substantially to the understanding of teacher learning. Yet, research on learning to teach English pronunciation is still in its infancy with the aim of this article being the exploration of the longitudinal development of four L2 instructors' practices and cognitions about English pronunciation pedagogy. Qualitative data were collected in three phases over six years, ranging from the beginning of a pronunciation pedagogy course into the teacher's current professional careers. Pre- and post-course questionnaires, a course assignment, focus groups, observations, narrative frames, and semi-structured interviews were triangulated to produce detailed teacher profiles, which then provided a thorough understanding of the practitioner's developing practices and cognitions. Findings demonstrated complex and continuous yet nonlinear and individual development, especially in two areas: (i) the teachers' delivery of pronunciation instruction and (ii) their focus on pronunciation pedagogy. Four specific factors were also identified as impacting the developmental process of teachers' practices and cognitions about pronunciation. In light of these findings, the article concludes with a recommendation to extend an existing framework for preparing pronunciation teachers.